Asset Repairon the Corruption Eradication Commission: Strategies in the Fight against Corruption in Indonesia - RA Gismadiningrat; Eva Achjani Zulfa; Surya Nita (Budapest International Research and Critics University, 2023)
The phenomenon of corruption as an extraordinary crime in Indonesia shows the existence of endemic corruption, which is accompanied by the emergence of significant losses to the state's finances. Efforts to enforce the law through the application of corporal punishment (prison) fines or additional punishment in the form of replacement money have not turned out to be maximal in rescuing stolen assets so that the state remains the victim. Asset recovery is one of the goals of new punishment and is one of the strategies of the Corruption Eradication Commission in dealing with criminal acts of corruption, but the implementation of asset recovery is not easy, the perpetrators always have various new and sophisticated modus operandi to hide/obscurate assets resulting from corruption, so that they are not traced. . This article aims to answer research: The research method uses empirical normative juridical research, with a statute approach and a case approach.. Through the application of the Balanced Probability Principle Theory and Non Conviction Based Asset Forfeiture, the mechanism for tracking money and following assets using money laundering and civil lawsuits articles needs to be placed as the main legal remedy besides criminal law enforcement, so that the implementation of asset recovery at the Corruption Eradication Commission can be carried out maximally.